Gaya Kepemimpinan Kepala Sekolah Smk Ulil Albab Desa Kelutan Kecamatan Ngronggot Kabupaten Nganjuk - Fatahuddin (INOVATIF: Jurnal Penelitian Pendidikan, Agama, dan Kebudayaan, 2020)
The leader is expected to be able to influence his subordinates so that they can maximize their functions to be able to achieve the goals set. The Principal as a professional leader who is given the task of leading an institution to determine effective steps in the school environment, in order to achieve goals. In Ulil Albab Vocational School Kelutan Ngronggot Nganjuk if you want something good and matters related to the school run smoothly, the Principal of Ulil Albab Vocational School as the school leader always talks with the council Teachers and school staff for the best decision making, and the results of the deliberations are agreed by the Principal of Ulil Albab, the council of Teachers, employees, so that all involved must feel responsible as well. Head of Ulil Albab School Kelutan Ngronggot Nganjuk in his communication patterns such as father to his son and leader to his subordinates and like friends to the elders, sometimes exemplifies a professionalism in working for the entire Teacher board and employees. Principal Ulil Albab Kelutan Ngronggot Nganjuk he tends to deliberate, give direction, order and give an example of goodness in SMK Ulil Albab, he is more concerned with the public interest than personal interests and he also assigns tasks to his subordinates according to his abilities, also all teachers and school staff Ulil Albab Vocational School is considered as their own family. He tends to use the type of Democracy in managing schools.